Plant nervous system - Qamaruz Zaman, Faridah; Mohd Nor, Nurul Ayuni (Universiti Putra Malaysia Press, 2016)
The Venus flytrap (Dionaea muscipula: Droseraceae) has one of the most rapid movements in the plant kingdom. It can catch insects with its toothed modified leaves that snap shut when triggered by prey, touching the tiny hairs on the inner leaf surface.